Public Relations Strategies in Building Brand Awareness at CV. Borong Persada - Elyana Putri Nazalia; Gravela Melleyuandita Annisa (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Public relations strategy is a program plan or steps that play a major role in building Brand awareness. CV Borong Persada is a company engaged in the field of construction and procurement of goods and services. Its main focus is to cooperate with various government agencies related to the procurement of goods and services. This study aims to determine and obtain a descriptive picture of Public relations strategies in building Brand awareness. This research uses the concept of Public relations mix strategy from the development of Thomas L. Harris, namely the Public relations mix strategy consisting of PENCILS components. Information collection techniques are in-depth interviews, observations, literature studies and other data sources. Using the post-positivist paradigm and descriptive qualitative approach, the results showed that CV Borong Persada successfully implemented PENCILS and received a positive response from the public, but there needs to be a more presentative and planned Public relations strategy in order to gain greater power and increase Brand awareness of this company. This study contributes to the existing knowledge on Public relations and Brand awareness, as well as providing practical insights for organizations looking to improve their brand reputation.